Developing a Resource Model of Power and Authority in Anonymous Online Criminal Interactions - Newsome, Helen; Grant, Tim (Language and Law / Linguagem e Direito, 2024)
The purpose of this paper is to provide both a theoretical foundation and a practical framework for analysing power and authority in online interactions, for application in forensic linguistic contexts. In online discussion fora differences in institutional or social power are often obscure and posters may be anonymous. This lack of contextual knowledge can create a challenge for the analyst in finding a framework to theorise, explore, and describe these sorts of power performance. In this paper, we provide a framework to describe the basis on which individuals make claims to power and use this framework to explore the nature and distribution of power across different fora of both criminal and benign intent. This is developed through an analysis of three online discussion fora, of approximately 160,000 words, resulting in a framework of eight main categories of power resource. This allows us to contrast the three fora, showing differences in the nature and distribution of power resource, and also enables description of individuals as high-resource or low-resource with regards to their claims to power. This theory and framework can also be productive in the analysis of language and power in computer mediated communication (CMC) more widely.